Overexpression of c-Myb is associated with suppression of distant metastases in colorectal carcinoma - Tichý, Michal; Knopfová, Lucia; Jarkovský, Jiří; Pekarčíková, Lucie; Veverková, Lenka; Vlček, Petr; Katolická, Jana; Čapov, Ivan; Hermanová, Markéta; Šmarda, Jan; Beneš, Petr (Tumour biology, 2016)
The MYB gene codes for the c-Myb transcription factor maintaining proliferation of colon epithelial progenitors, thus controlling colon development and homeostasis. This gene is overexpressed in early phases of colorectal cancer (CRC) tumorigenesis. The aim of this study was to examine the expression of c-Myb in CRC tissue samples both at the messenger RNA (mRNA) and protein levels and to evaluate their associations with clinicopathological characteristics in a group of 108 CRC patients. Statistically significant negative association was found between the frequency of the c-Myb-positive tumor cells assessed by immunohistochemistry and the presence of distant metastases (p < 0.01) but not tumor differentiation, tumor stage, lymph node involvement, vascular invasion, tumor localization, age, and gender of the patients. Although the c-Myb protein level in the tumor tissue correlated with its mRNA level, no significant association between MYB mRNA and any clinicopathological characteristics was observed. We conclude that albeit overexpression of c-Myb is considered as an important factor contributing to early phases of CRC tumorigenesis, it may later have negative effect on tumor cell dissemination as observed recently in breast cancer as well. Further studies are required to explain the role of c-Myb during formation of CRC distant metastases.
Keywords: regulace genové exprese u nádorů; dospělí; Proto-Oncogene Proteins c-myb; kolorektální nádory; Female; c-Myb; Lymphatic Metastasis; lymfatické metastázy; Adult; invazivní růst nádoru; ženské pohlaví; protoonkogenní proteiny c-myb; Colorectal Neoplasms; Gene Expression Regulation, Neoplastic; RNA nádorová; Immunohistochemistry; buněčná diferenciace; lidé; messenger RNA; Aged, 80 and over; RNA, Messenger; Colorectal cancer; Down-Regulation; Adenocarcinoma; Male; geny myb; Aged; adenokarcinom; nádorové proteiny; Neoplasm Proteins; Metastases; Genes, myb; RNA, Neoplasm; lidé středního věku; Cell Differentiation; senioři nad 80 let; down regulace; senioři; mužské pohlaví; mRNA; Neoplasm Invasiveness; Middle Aged; Humans